Expanding the Spectrum of Ciliated Muconodular Papillary Tumor of the Lung: A Case Showing Nonpapillary and Purely Glandular Morphology. Issue 6 (November 2018) - Baratelli, Felicita; Wei, Christina; Elatre, Wafaa; Xiao, Guang-Qian; Ward, Pamela; Pettersson, Jonas; Campan, Mihaela; Larsen, Brandon T.; Ashley, Prosper; Wang, Linan; Cohen, Robbin; Koss, Michael
Abstract : Abstract: We report an unusual case of a subpleural bronchiolar/glandular proliferation in a 76-year-old Hispanic woman with microscopic features reminiscent of those of the so-called ciliated muconodular papillary tumor (CMPT). The lesion presented radiologically as a solitary subpleural nodule measuring 2.7 × 1.2 cm with low standard uptake value (SUV) of 1.4. Microscopically, it was circumscribed but unencaspulated and consisted of mucous-filled spaces lined by cytologically bland cuboidal to low columnar cells, including goblet cells and ciliated epithelium, with underlying nodular collections of basaloid cells. The lining cells stained diffusely for CK7 but only focally for TTF-1 and CEA, whereas the basal cells expressed CK5/6. Ki-67 showed a proliferative index of less than 1%. Target gene mutation analysis with a 50-cancer-related-gene panel using next-generation sequencing showed the bronchiolar proliferation to harbor an EGFR in frame exon 20 insertion mutation with 30% allele frequency, which supports a neoplastic diagnosis. Accordingly, given the mutually exclusive nature of driver mutations, a BRAF V600E mutation was absent by both immunohistochemical and next-generation sequencing analysis. Microscopic evidence of metastatic spread was not seen in 8 regional lymph nodes examined. Given the histomorphology and immunohistochemical findings, the mutational profile and the reported heterogeneous microscopic patterns of CMPTs, including glandular component, we suggest the tumor herein described be a glandular variant of CMPT. We therefore suggest that the term ciliated muconodular tumor may be more appropriate for this group of lesions.